The Role Of Artificial Intelligence In Higher Education And Research - Dr. Sarika Gupta, Dr. Anandvardhan; Dr. Sanjeet Kumar Gupta (Journal of Informatics Education and Research, 2025)
Artificial Intelligence (AI) is no longer an abstract idea or distant technology it is actively changing the pattern of universities teachings and conduction of research. From personalized tutoring systems to research automation and predictive analytics, AI is creating every new possibility in higher education. But with rapid adoption come serious questions around ethics, data privacy, transparency, and the shifting role of human educators. This article explores the practical applications of AI across teaching and research, while also examining the emerging risks and gaps in current implementation particularly the lack of governance frameworks in shades of Western regions. The goal is to offer a grounded understanding of both potential and pitfalls, and propose actionable strategies for ethical adoption of AI in Higher Education.